SOCIO-PSYCHOLOGICAL STATES OF ADOLESCENTS IN MODERN SOCIETY - Yusupova Firuza Yuldashovna (Web of Journals Publishing, 2024)
This article explores the socio-psychological states of adolescents in modern society as well as the age characteristics of adolescent periods of crisis. It also talks about individual psychological characteristics found in adolescents.
Keywords: adolescent, individuality, health, hygiene, psychological characteristics, determinism, age periods.